2010
DOI: 10.1111/j.1600-0501.2010.02068.x
|View full text |Cite
|
Sign up to set email alerts
|

Guided bone regeneration with a synthetic biodegradable membrane: a comparative study in dogs

Abstract: Objectives: The aim of the present study was to compare a newly developed biodegradable polylactide/polyglycolide/N-methyl-2-pyrrolidone (PLGA/NMP) membrane with a standard resorbable collagen membrane (RCM) in combination with and without the use of a bone substitute material (deproteinized bovine bone mineral [DBBM]) looking at the proposed tenting effect and bone regeneration. Materials and methods: In five adult German sheepdogs, the mandibular premolars P2, P3, P4, and the molar M1 were bilaterally extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 19 publications
1
31
0
3
Order By: Relevance
“…Human histological data from earlier time points, however, are not available from the literature. Fragmentation of the test membrane, as it was reported in an earlier preclinical study when used without any bone substitute material, was not histologically observed in the present study (Jung et al 2011).…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Human histological data from earlier time points, however, are not available from the literature. Fragmentation of the test membrane, as it was reported in an earlier preclinical study when used without any bone substitute material, was not histologically observed in the present study (Jung et al 2011).…”
Section: Discussionsupporting
confidence: 41%
“…In a recent preclinical investigation, it was demonstrated that the membrane was totally fragmented after 6 months and completely resorbed after 12 months (Nieminen et al 2006). In another study in dogs, the histological analysis revealed that the test membrane was broken into pieces due to its stiffness and brittleness when the membrane was not supported by grafting materials (Jung et al 2011). Therefore, the tenting effect of the PLGA/NMP membrane was apparently not sufficient to maintain the space for regeneration.…”
Section: Discussionmentioning
confidence: 96%
“…It can be used as a space filler 10,11,[19][20][21] or a membrane. 2,22,23 In our study, we used PLGA copolymer in the form of scaffolds. The scaffold serves to provide a temporary structure for cells to proliferate and maintain their differentiated function before being resorbed by the body.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] One candidate for such a substitute is cyanoacrylate glue. Cyanoacrylate is a tissue-adhesive material that promotes the rapid adhesion of soft and hard tissues.…”
mentioning
confidence: 99%